Switching the reaction pathways of electrochemically generated β-haloalkoxysulfonium ions – synthesis of halohydrins and epoxides - Shimizu, Akihiro; Hayashi, Ryutaro; Ashikari, Yosuke; Nokami, Toshiki; Yoshida, Jun-ichi (Beilstein Journal of Organic Chemistry, 2015)
β-Haloalkoxysulfonium ions generated by the reaction of electrogenerated Br+ and I+ ions stabilized by dimethyl sulfoxide (DMSO) reacted with sodium hydroxide and sodium methoxide to give the corresponding halohydrins and epoxides, respectively, whereas the treatment with triethylamine gave α-halocarbonyl compounds.
Keywords: DMSO; electrosynthesis; epoxides; halohydrins; halogen cations

Onium ions - Olah, G. A.; Laali, K. K.; Wang, Q.; Prakash, G. K. S. (Wiley, 1998)

(untitled) - Rodriguez, J.; Dulcère, J.-P. (Synthesis, 1993)

(untitled) - Chaikovski, V. K.; Kharlova, T. S.; Filimonov, V. D.; Saryucheva, T. A. (Synthesis, 1999)

(untitled) - Moeller, K. D. (Tetrahedron, 2000)

(untitled) - Sperry, J. B.; Wright, D. L. (Chem. Soc. Rev., 2006)

(untitled) - Yoshida, J.; Kataoka, K.; Horcajada, R.; Nagaki, A. (Chem. Rev., 2008)

(untitled) - Kirste, A.; Elsler, B.; Schnakenburg, G.; Waldvogel, S. R. (J. Am. Chem. Soc., 2012)

(untitled) - Finney, E. E.; Ogawa, K. A.; Boydston, A. J. (J. Am. Chem. Soc., 2012)

(untitled) - Sumi, K.; Saitoh, T.; Natsui, K.; Yamamoto, T.; Atobe, M.; Einaga, Y.; Nishiyama, S. (Angew. Chem., Int. Ed., 2012)

(untitled) - Morofuji, T.; Shimizu, A.; Yoshida, J. (J. Am. Chem. Soc., 2013)

(untitled) - Yamaguchi, Y.; Okada, Y.; Chiba, K. (J. Org. Chem., 2013)

(untitled) - Yoshida, J.; Suga, S.; Suzuki, S.; Kinomura, N.; Yamamoto, A.; Fujiwara, K. (J. Am. Chem. Soc., 1999)

(untitled) - Suga, S.; Suzuki, S.; Yamamoto, A.; Yoshida, J. (J. Am. Chem. Soc., 2000)

(untitled) - Yoshida, J.; Suga, S. (Chem. – Eur. J., 2002)

(untitled) - Suzuki, S.; Matsumoto, K.; Kawamura, K.; Suga, S.; Yoshida, J. (Org. Lett., 2004)

(untitled) - Suga, S.; Matsumoto, K.; Ueoka, K.; Yoshida, J. (J. Am. Chem. Soc., 2006)

(untitled) - Matsumoto, K.; Sanada, T.; Shimazaki, H.; Shimada, K.; Hagiwara, S.; Fujie, S.; Ashikari, Y.; Suga, S.; Kashimura, S.; Yoshida, J. (Asian J. Org. Chem., 2013)

(untitled) - Miller, L. L.; Kujawa, E. P.; Campbell, C. B. (J. Am. Chem. Soc., 1970)

(untitled) - Miller, L. L.; Watkins, B. F. (J. Am. Chem. Soc., 1976)

(untitled) - Midorikawa, K.; Suga, S.; Yoshida, J. (Chem. Commun., 2006)

(untitled) - Shono, T.; Matsumura, Y.; Katoh, S.; Ikeda, K.; Kamada, T. (Tetrahedron Lett., 1989)

(untitled) - Ashikari, Y.; Shimizu, A.; Nokami, T.; Yoshida, J. (J. Am. Chem. Soc., 2013)

(untitled) - Kornblum, N.; Powers, J. W.; Anderson, G. J.; Jones, W. J.; Larson, H. O.; Levand, O.; Weaver, W. M. (J. Am. Chem. Soc., 1957)

(untitled) - Mancuso, A. J.; Swern, D. (Synthesis, 1981)

(untitled) - Phan, T. B.; Nolte, C.; Kobayashi, S.; Ofial, A. R.; Mayr, H. (J. Am. Chem. Soc., 2009)

(untitled) - Ashikari, Y.; Nokami, T.; Yoshida, J. (J. Am. Chem. Soc., 2011)

(untitled) - Ashikari, Y.; Nokami, T.; Yoshida, J. (Org. Biomol. Chem., 2013)

(untitled) - Schmidt, B. (Pure Appl. Chem., 2009)

(untitled) - Enders, D.; Hüttl, M. R. M.; Grondal, C.; Raabe, G. (Nature, 2006)

(untitled) - Yoshida, J.; Saito, K.; Nokami, T.; Nagaki, A. (Synlett, 2011)

(untitled) - Suga, S.; Yamada, D.; Yoshida, J. (Chem. Lett., 2010)

(untitled) - Brimeyer, M. O.; Mehrota, A.; Quici, S.; Nigam, A.; Regen, S. L. (J. Org. Chem., 1980)

(untitled) - Gianini, M.; von Zelewsky, A. (Synthesis, 1996)

(untitled) - Majetich, G.; Shimkus, J.; Li, Y. (Tetrahedron Lett., 2010)

(untitled) - Fenselau, A. M.; Moffatt, J. G. (J. Am. Chem. Soc., 1966)